[An assessment of malaria diagnostic capacity and quality in Ghana and the Republic of Benin] - KEDOTE, MARIUS; KEATING, Joseph (My University, 2014)
Background: In malaria–endemic countries, the absence of parasitological confirmation of malaria infection potentially results in overtreatment of non-malaria febrile illness with antimalarial drugs; this may lead to health- care workers (HCW) missing other treatable illness or wastage of resources. This paper presents results from nationally representative assessments of malaria diagnostic accuracy, quality and capacity in Ghana and the Republic of Benin. Methods: Cross-sectional surveys were conducted in December 2012 among a representative sample of health facilities (n¼30 per country), using a modified service provision assessment, followed by HCW observations and interviews. To analyze the data we used x2 statistics and logistic regression. Results: Malaria microscopy and rapid diagnostic test interpretation was accurate most of the time in both countries. Drugs were generally prescribed in line with positive malaria test results (Ghana: 85.4%, 95% CI 72.2–98.7; Benin: 83.6%, 95% CI 68.7–98.4), although some patients with negative malaria test results still received treatment (Ghana: 30.1%, 95% CI 11.1–49.0; Benin: 37.8%, 95% CI 22.6–53.0). Conclusions: Diagnostics for malaria are often performed adequately and accurately in Ghana and Benin, although diagnostic coverage within facilities remains incomplete and some individuals who test negative for malaria receive antimalarial drugs.
Keywords: Benin; Diagnostic; Ghana; Health facility; Malaria; Rapid assessment